Time Series Analysis and Optimization of the Prediction Model of Agricultural Insurance Loss Ratio - YU, WANG; Muhammad Asraf, Abdullah; Josephine Yau, Tan Hwang (Nan Yang Academy of Sciences Pte. Ltd., 2024)
For ensuring successful ϐinancial planning to perform sustainable farming, one key sector is to provide solu‑ tions that could accurately predict the agricultural loss ratios. In China, the Henan province is considered to be an agricultural center that is primarily exposed to drastic weather ϐluctuations that directly impact the crop yields. This study was conducted in Henan province from January 2020 to December 2023. With the data collected from that period, the study proposes a combinatory model combining Deep Gaussian Processes with Bayesian Long Short‑ Term Memory (LSTM) networks. The model was trained on data encompassing weather conditions, agricultural practices, and historical insurance claims. The experimental analysis was conducted against other traditional mod‑els, including ARIMA and Support Vector Regression. The RMSE improvement of the proposed model was around 7.2% on training data and 8.2% on test data, which demonstrates enhanced predictive accuracy. The enhanced per‑formance of the proposed model was reϐlected in its effectiveness in reducing log‑likelihood errors across training epochs. The model had demonstrated better robustness in handling complex and multi‑dimensional agricultural data.